The employment of a nonfumigant nematicide for control of the root-knot and lesion nematodes on yams and crop preservation in storage: Uso de un nematicida no fumigante para combatir los nematodos noduladores y lesionadores en name y para la preservacion de la cosecha en almacenaje - Badra, T.; Steele, W.M.; Caveness, F.E. (1980)
The nematicidal efficacy of oxamyl as a non-fumigant nematicide in controlling damage caused by the root-knot nematode (Meloidogyne javanica) and the lesion nematode (Pratylenchus brachyurus) to the white yam (Dioscorea rotundata) was investigated under field and storage conditions. Infection of yams by these nematodes in the field affects the survival of tubers in storage and threatens the maintenance of yams as vegetatively propagated clones. Populations of M. javanica and P. brachyurus in the yam root and tuber rhizoshere increased markedly during the growing season in untreated controls. Oxamyl 10G applied at the rate of 6 kg a.i./ha as row treatment was most effective in the control of M. javanica, whereas oxamyl 24L applied at the rate of 6 kg a.i./ha as a foliar spray was most effective in the control of P. brachyurus (b= -7.1 and -5.3, respectively). Tuber yields were increased by 49 and 42 percent over untreated controls when granular oxamyl at 3 kg a.i./ha was combined with calcium nitrate or ammonium sulphate at 180 kg N/ha, respectively (P = 0.01).